P-241 Leading the way – creating a diverse trustee board. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Webb, Robin
Abstract : Background: 62% of top charities have all-white boards, according to Inclusive Boards (2018), and the report 'Taken on trust: the awareness and effectiveness of charity trustees in England and Wales' (2017), found 71% of trustees were approached to join either directly by the chair or fellow board members. Insanity is often defined as: 'Doing the same thing over and over again and expecting different results'. We need to build diverse boards that bring in a wide range of talent, skills and experiences. Therefore, we must be intentional in our recruitment for these key roles. This will ensure we have the best people to lead our organisations in these interesting times. Aims: To recruit a diverse mix of new trustees to our board with a variety of skills and experiences as part of our plan to build and develop a high performing Board. Method: June to August 2017 – Trustees reviewed skills by self–assessment. In context of our strategic development plans gaps in skills identified. September to October 2017 – extensive advertising; national newspaper (Guardian), non–exec recruitment websites, local media, case studies in publications October 2017 – 2 × open evenings held for people interested in exploring the role to meet existing trustees and Exec. directors November 2017 – applications shortlisted, formal interviews held December 2017 – new trustees appointed. Results: 22 people attended two open evenings; 17 applications received; 14 interviewed; five appointed. Skills and experience recruited included two lawyers, investment and financial expertise, medical management and local government. Four women, one man. Three from non white English backgrounds. Four aged 42-51 and one in 60s. It is too early to evaluate the impact of this greater diversity on the effectiveness of the Board; a review is planned for 2019. Conclusion: Our past experience and published research confirms that trustees recruiting their friends results in similar people from similar background joining charity Boards. If charities want to build greater diversity on their boards, drawing in a wider range of skills, experience and backgrounds then being intentional about the approaches they take can deliver these ambitions.